2018
DOI: 10.1136/bmjstel-2017-000259
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of childbirth improves clinical management capacity and self-confidence in medical students

Abstract: Background The learning process of physiological mechanisms of childbirth and its management are important elements in the education of medical students. In this study, we verify how the use of a high-fidelity simulator of childbirth improves competence of students in this regard. Methods A total of 132 medical students were recruited for the study in order to attend a physiological childbirth in a no-hospital environment after being assigned to two groups. The control group received only a normal cycle of lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Medical simulation, especially low-fidelity, allows learning how to perform medical procedures in comfortable conditions and without a risk for patients. Mannell et al [26] found that the use of high-fidelity simulation significantly increased the absorption of knowledge and practical skills related to receiving physiological delivery among medical students. Other authors specify that already two or three 45-minutes sessions during which each student had the opportunity to receive delivery twice in a session was adequate to obtain minimum competence 6 months after the training.…”
Section: Simulation Impact On Patient Treatment Resultsmentioning
confidence: 99%
“…Medical simulation, especially low-fidelity, allows learning how to perform medical procedures in comfortable conditions and without a risk for patients. Mannell et al [26] found that the use of high-fidelity simulation significantly increased the absorption of knowledge and practical skills related to receiving physiological delivery among medical students. Other authors specify that already two or three 45-minutes sessions during which each student had the opportunity to receive delivery twice in a session was adequate to obtain minimum competence 6 months after the training.…”
Section: Simulation Impact On Patient Treatment Resultsmentioning
confidence: 99%
“…Hi-delity simulation has been demonstrated to meliorate competencies (Issenberg et al, 2005), de ne professional competence (Epstein and Hundert, 2002), improve patient outcomes (Cook et al, 2011), and develop and enhance teamwork (Baker et al, 2006) (Shapiro et al, 2004). Epecially in obstetrics, simulation is increasingly used for training of adverse and low-frequent events, such as shoulder dystocia (Mannella et al, 2016) or vacuum application (Mannella et al, 2021) or for didactic purposes (Mannella et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As in many University hospitals, authors have, over time, adopted simulation in obstetrics for standard training of medical students, 14 midwives, and obstetrical/gynecologic residents 15 . This is an added value for understanding the mechanical aspects of birth and for acquiring technical skills to diagnose and manage labor.…”
Section: Discussionmentioning
confidence: 99%